Assistance of Indigofera Cultivation as Batik Natural Dyes in Kampung Alam Malon, Gunungpati Semarang - Ning Setiati; Ely Rudyatmi; Krispinus Kedatipukan; Dyah Rini Indriyanti (Journal of Dedicators Community, 2021)
This community service aim to motivate kelompok Tani Gunungpati 03 Kampung Alam Malon and kelompok Tani Gunungpati 02 Nglarang, Gunungpati to start planting Indigofera. Production can be used to fulfill a part of batik natural dye for cheaper. Special target is availability qualified Indigofera with criteria dark green leaves (green bluish) and oval shape with brownish black seed. The target is from 1000 seeds can be generate 1000 qualified plant ready to harvest in 3 months, and next re-harvest in 2 months. Some activities already done such as socialization community service attended by 36 of farmer team and they held active discussion about the use and additional income from planting indigo. Training in make natural dye paste from indigo is given to 15 of farmer team by experienced trainer. The result of this activity were the farmer group be able to cultivate indigofera, built 2 water shelter to drainage indigo plant. The result of seedlings is not satisfied yet because the growth of sprouts were not simultaneously and not applying hormone gibrelin technology so that for next step need revision in raise seeding. The farmer group ca easily harvest their indigofera to make paste for batik dye color